The Edinburgh companion to literature and sound studies - Groth, Helen; Murphet, Julian (Edinburgh companions to literature and the humanities., 2024)
This field-defining collection maps key intersections between sound studies and literary studiesProvides a unique focus on literary applications of sound studies researchFeatures a wide range of international, emergent and established scholarsInterdisciplinary work throughoutConsiders a broad range of historical periodsFeatures entirely new commissioned work; no republished material available elsewhere is includedCollections on sound studies have seldom explored the vexed relationship between literature - a medium largely defined by its silence - and the dynamics and technologies of sound. This Companion is designed to help sound studies scholars grapple with the auditory capacities of text and encourage literary scholars to take full cognisance of the rich soundscapes mapped, or created, by texts read quietly. The essays assembled here consider a broad range of sound studies topics, including music in writing; the inscription of listening; worlding through sound; military and industrial noise; the gender of sound; racialised soundscapes; theatrical sounds; literature and sound media; and sonic epistemology. Helen Groth and Julian Murphet present a comprehensive set of new research on the relationship between sound and writing over time from a range of eminent, established and emerging sound studies scholars.